Odpowiedź:
(7 - 5 i 2/5) * 1/4 = (6 i 5/5 - 5 i 2/5) * 1/4 = 1 i 3/5 * 1/4 = 8/5 * 1/4 = 2/5
(7/9 - 47/72) : 1 i 1/4 = (56/72 - 47/72) : 1 i 1/4 = 16/72 * 4/5 = 16/90 = 8/45
6 * (1 i 1/3)² = 6 * (4/3)² = 6 * 16/9 = 32/3
(5/7)² : 5/7 = 25/49 * 7/5 = 5/7
(1/3 - 1/4)² = (4/12 - 3/12)² = (1/12)² = 1/144
(2/5)² + 4 i 1/2 * 2 i 2/3 = (2/5)² + 9/2 * 8/3 = (2/5)² + 12 = 4/25 + 12 = 12 i 4/25
5 * (1/2)² + 15 * (1/3)² = 5 * 1/4 + 15 * 1/9 = 5/4 + 15/8 = 10/8 + 15/8 = 25/8 = 3 i 1/8
1/9 - (5/6 - 2/3)² = 1/9 - (5/6 - 4/6)² = 1/9 - (1/6)² = 1/9 - 1/36 = 4/36 - 1/36 = 3/36 = 1/12